Analisis SWOT Pelabuhan Ferry International Sekupang - Rusda Irawati; Benny Syahroni (Politeknik Negeri Batam, 2013)
This research was held in Sekupang Internasional Ferry Terminal (SFT) as a public seaport for the internasional crossroad from Batam-Indonesia to the Front Harbour of Singapore. The purpose of this research are: to know about SFT’s factors of strength, weakness, opportunity and threat, to know and analyze about SFT’s competitives profile. The research used quantitative and desciptive method. It’s used to measure internal and external factor and the SFT’s competitive profile. Furthermore composing IE matrix to know the position of the company. The result of this reseach showed that, the main strenght of SFT are physical resources. The main weaknesses of the SFT are location of the port far from city centre and low of market share. Main opportunities for the companies are distance travelled closer to port of Singapore. The greatest threat are there is a special port that serves the public passenger and a rise in seaport taxes also one should be wary of threats by the company.